Mechanisms for homogeneous and heterogeneous formation of methane during the carbon–hydrogen reaction over zigzag edge sites. (June 2016) - Calderón, Lucas A.; Chamorro, Eduardo; Espinal, Juan F.
Abstract: Methane is the main product in the reaction between molecular hydrogen and carbonaceous materials such as char, graphene and graphite. Although, pathways for the formation of methane in the carbon-hydrogen reaction have been proposed attending to experimental and molecular modeling results, there is not compelling evidence of the elementary character of the steps in such pathways. In this work we propose possible mechanisms with details at molecular level that account for the formation of methane at the zigzag edge through elementary steps using molecular modeling within the framework of the density functional theory. These mechanisms involve saturation of reactive sites, hydrogenation of the edge, ring opening and desorption of methyl groups or direct desorption of methane. Thermodynamic and kinetic details for all steps were explored over temperature and pressure ranges going from 298 K to 1500 K (at 0.1 MPa) and 0.1 MPa–10 MPa (at 1100 K), respectively. The proposed mechanisms show a remarkable qualitative agreement between predicted behavior of overall state functions (Δ H tot, Δ S tot, and Δ G tot ) and the equilibrium constant for the formation of methane and the observed experimental behavior of these thermodynamic quantities for standard formation of methane from 298 K to 1500 K.